Factors to consider from education to promote an image of science and technology with a gender perspective - Martín-Gámez, Carolina; García-Durán, Desirée; Fernández-Oliveras, Alicia; Torres-Blanco, Verónica (Elsevier, 2022)
The image of science influences on the decision of girls when opting for studies related to STEM disciplines, since in many cases they are perceived as masculine, due to the image promoted from different areas of society, including the education system. Consequently, women do not feel identified with these disciplines, and prejudices and beliefs are generated that promote the well-known gender gap that exists in these areas. Therefore, this article sets out the considerations to be taken into account from science and technology education to avoid showing an image of science as individual, stereotyped and elitist, among other aspects, and, ultimately, to promote an image of science and technology with a gender perspective. It is necessary to transform curricular content and teacher training following these considerations, so that students perceive a realistic image of science and technology. This will have a positive influence by minimising the Pygmalion effect that occurs in girls and helping to combat social inequality that generates the under-representation of women in scientific-technological fields.
Keywords: Igualdad de género; Educación; Psicología de la educación; Mujeres en la ciencia -- Educación; Image of science; Education; Gender perspective; STEM